Flexible Pathways into the German Labor Market (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Germany’s labor market faces persistent skills shortages alongside rising levels of migration and a growing number of adults without formally recognized qualifications. While Germany’s dual vocational education and training (VET) system has historically delivered strong employment outcomes, its qualification-centric structure creates significant barriers for migrants, refugees, and formally low-skilled workers whose competences are often acquired informally or abroad. This paper presents a flexible, modular integration pathway based on partial qualifications (Teilqualifikationen) as a pragmatic middle ground between full vocational qualifications and purely skills-based approaches. Drawing on labor market intelligence from JOBMONITOR, competence identification tools such as my-professional-experience.org and MYSKILLS, and modular training provision through MYTQ, the paper illustrates how demand-driven skills assessment, validation, and step-by-step upskilling can be aligned across regions and occupations. Empirical evidence from online job advertisements, validation practice, and program evaluations demonstrates that partial qualifications correspond closely to actual employer demand and offer viable entry points into employment while preserving pathways to full certification. The paper concludes with policy recommendations for standardizing partial qualifications, integrating them into formal validation frameworks, and strengthening their role in sustainable labor market integration for migrants and other disadvantaged groups.Keywords: Partial qualifications; skills recognition; validation of prior learning; migrant labor market integration; vocational education and training; skills-first approaches; Germany; modular learning pathways; labor market intelligence; workforce development